Intuit QuickBooks enterprise edition 12.0 cookbook for experts : 60 plus recipes to save time and increase effectiveness in data entry, supervision, and business management for both public and industry accountants /: 60 plus recipes to save time and increase effectiveness in data entry, supervision, and business management for both public and industry accountants. (©2012) - Unknown
No abstract available